The Concept of Character Education from the Perspective of Al-Qur’an and Hadith - Sakinah, Dini Yanti (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Character education is the main support of the educational process, as an effort to give birth individuals with Islamic personalities. As Muslims, adhering to the Al-Qur'an and As-sunnah is a mustÂ because both, Muslims act and solve a problem. This study aims to understand the formulation of the character education concept in the perspective of Al-Quran and Hadith. Through studying understanding textually and contextually. Data collected from various references; both primary, secondary, and supporting data. The results showed the hadiths and the verses of Al-Qurâ€™an raised in this study contained characters or behaviors towards God, oneself, fellow humans, and their environment. Some of the character education concepts that can be revealed from the Al-Quran and the Hadith are First, the concept of character education, Second. The concept of character education in Islam. Third, the foundation of character education. Fourth, the method of internalizing character education.